Pregnancy outcomes in bone marrow disorders: a tertiary care experience - Rao Preethi Venkatachala; C N Sheela (Barpeta Obstetrics and Gynaecological Society, 2021)
Objectives: To study the maternal and foetal outcomes in pregnancies complicated by bone marrow disorders. Material and methods: A retrospective descriptive study of women with bone marrow disorders in pregnancy, between January 2011 and January 2016 was carried out. Their antenatal and labour records were reviewed and demographic details noted. The primary outcome measures studied were - severity of anaemia, additional drugs required during pregnancy, gestational age at delivery, requirement of transfusion of blood and blood products and mode of delivery. Obstetric and medical complications and neonatal outcomes were the secondary outcome measures noted. Blood counts during pregnancy and after delivery were noted. Data are presented as descriptive statistics including means and percentage. Results: Prevalence of bone marrow disorder complicating pregnancy was (10/12420) 0.08%. 6 women had aplastic anaemia, 2 had CML, 1 had AML and 1 had myelodysplastic syndrome. 50% were in remission; 60% received drugs for bone marrow disorder. Antenatal complications like preeclampsia (40%), oligohydramnios (40%), infections, IUGR and IUD (30% each), preterm labour, previous caesarean delivery (20% each) and PNH (10%) were noted. 50% had moderate anaemia, 30% severe anaemia, 90% had thrombocytopenia. Transfusion of blood products was required in 30% antepartum, 70% intrapartum and 60% postpartum. 50% had vaginal delivery. There was no PPH or maternal mortality. 70% took home healthy babies. Conclusion: Multidisciplinary approach, preconceptional counseling, good antenatal care, delivery at a tertiary care centre, prompt treatment of infections and sepsis, prophylactic transfusions and optimal use of chemotherapeutic drugs can ensure successful pregnancy.